RETIREMENT FUND PAYMENT SYSTEM BASED ON FINANCIAL LITERACY LEVEL AMONG CIVIL SERVANTS IN GORONTALO PROVINCE - Adam, Sulistiawati; Dama, Hais; Pongoliu, Yayu Isyana (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine the influence of financial literacy levels on the retirement fund payment system. This research uses a descriptive quantitative method. The population is 31,800 civil servants (ASN) in Gorontalo, including civil servants from Gorontalo Provincial Government and Gorontalo Regency/City Governments. The sample size selected is 100 civil servants. The data collection technique uses questionnaires/surveys. Data analysis techniques include descriptive statistical analysis, goodness-of-fit, overall model fit test, Wald test, coefficient of determination, and hypothesis testing using logistic regression. Based on the research, it is found that financial literacy levels partially influence the retirement fund payment system. Civil servants with low financial literacy levels tend to prefer a monthly pension fund payment system, while those with high financial literacy levels prefer a lump-sum retirement fund payment system. Finally, those with average financial literacy prefer a monthly retirement fund payment system. Keywords: Financial Literacy; Retirement Fund Payment System; Civil Servant